Keseimbangan antara Ranah Akademis dan Ranah Pastoral dalam Model Penafsiran Prof. Dr. Ignatius Suharyo - Bhanu Viktorahadi (P3TK, Sanata Dharma University, 2019)
This paper aims to uncover the full extent of how the academic materials and learning models as employed by Prof. Dr. Ignatius Suharyo during his time as an active academic and practitioner of biblical hermeneutics or scriptural interpretation reflected his finest efforts to reconcile the two spheres of academia and the pastoral in regards to scriptural interpretations. Based upon research, the materials and academic models of Prof. Dr. Ignatius Suharyo, his readings and interpretations were found to be contributions of no small merit to the discipline. In turn, his contribution spearheaded various opportunities for the growth of scripture reading, no longer is the acadamically confined, but will therewith be scrutinized as an elaborate art of reading and interpretation under a new light.